2008
DOI: 10.1134/s1028334x08010327
|View full text |Cite
|
Sign up to set email alerts
|

Internal waves under an ice cover

Abstract: A theoretical model for propagation of internal waves under an ice cover is developed. The sea water is considered to be inviscid, non-rotating, and incompressible and the Brunt-Väisälä frequency is supposed to be constant. The ice is considered of uniform thickness, with constant values of Young's modulus, Poisson's ratio, density and compressive stress in the ice. The boundary conditions are such that the normal velocity at the bottom is zero and, at the undersurface of the ice, the linearized kinematical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Measurements of internal waves in a shallow fjord in Spitsbergen showed that fluctuations of temperature and velocity with a period of approximately 10 minutes and amplitude of internal waves about 1 m correlate with the fluctuations of the ice cover of the same period with an amplitude of a 5-8 millimeters [Marchenko et al, 2011]. These results agree with the theory [Muzylev, 2008]. One can distinguish a spectral peak at a frequency corresponding to a period of 10 min on the spectrum of bottom pressure measured with an SBE-39 pressure gauge on a submarine slope at a depth of 8 m.…”
Section: Internal Wavessupporting
confidence: 82%
“…Measurements of internal waves in a shallow fjord in Spitsbergen showed that fluctuations of temperature and velocity with a period of approximately 10 minutes and amplitude of internal waves about 1 m correlate with the fluctuations of the ice cover of the same period with an amplitude of a 5-8 millimeters [Marchenko et al, 2011]. These results agree with the theory [Muzylev, 2008]. One can distinguish a spectral peak at a frequency corresponding to a period of 10 min on the spectrum of bottom pressure measured with an SBE-39 pressure gauge on a submarine slope at a depth of 8 m.…”
Section: Internal Wavessupporting
confidence: 82%
“…In the present problem we consider tidally generated waves. For the semidiurnal tide M 2 we have ω = 1.4 × 10 −4 s −1 , which is much smaller than the buoyancy frequency for a continuous stratification normally found in Arctic waters, where N may range from 10 −3 to 5 × 10 −2 s −1 , according to Muzylev [2008]. Hence, the rigid‐lid approximation works well for the continuously stratified case.…”
Section: Mathematical Formulationmentioning
confidence: 80%
“…The presence of an ice cover will generally affect the propagation of gravity waves (see, e.g., Liu and Mollo ‐ Christensen [1988] in the case of surface waves). For internal waves in a continuously stratified ocean under ice, Muzylev [2008] showed that, because of the elastic properties of the ice, nonzero surface deflections occur for the lowest internal mode if the wave frequency ω is close to the buoyancy frequency N . However, when ω / N ≪ 1, corresponding to long waves, the rigid‐lid approximation (negligible vertical deflection under the ice) is very well fulfilled.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…In the "rigid lid" approximation, the vertical velocity at the surface is assumed to be equal to zero; therefore, due to the kinematic condition, the internal waves cannot cause any vertical displacements of the ice cover. Such conclusion is, however, inconsistent with the experimental data obtained for relatively deep parts of the Arctic Ocean [3][4][5][6] and also contradicts the theoretical results [7,8], according to which internal waves may be reflected in the fluctuations of the ice cover at frequencies comparable with the Brunt-Väisälä frequency. Scientists from the Shirshov Institute of Oceanology (Russian Academy of Sciences) and The University Centre in Svalbard (UNIS) carried out marine studies in the shallow Van Mijen Fjord in Svalbard to perform experimental tests of the theoretical conclusion concerning the possible influence of short internal waves on the fluctuations of the compact ice cover.…”
Section: Introductionmentioning
confidence: 65%
“…If the processes inside the ice cover are ignored the main equations and boundary conditions of the ice cover should be similar to the equations and conditions in the situation when the sea surface is free of ice. The only exception is the dynamic condition that may be expressed under the constant ice thickness h in the following form [7][8][9][10][11]:…”
Section: Brief Theory Of Internal Waves Under An Ice Covermentioning
confidence: 99%